Unsteady Free Convection Flow of a Micropolar Fluid With Newtonian Heating: Closed Form Solution - Hussanan, Abid; Mohd Zuki, Salleh; Khan, Ilyas; Razman, Mat Tahar (VINČA Institute of Nuclear Sciences, 2017)
This article investigates the unsteady free convection flow of a micropolar fluid over a vertical plate oscillating in its own plane with Newtonian Heating (NH) condition. The problem is modeled in terms of partial differential equations with some physical conditions. Closed form solutions in terms of exponential and complementary error functions of Gauss are obtained by using the Laplace transform technique. They satisfy the governing equations and impose boundary and initial conditions. The present solution in the absence of microrotaion reduce to well-known solutions of Newtonian fluid. Graphs are plotted to study the effects of various physical parameters on velocity and microrotation. Numerical results for skin-friction and wall couple stress are computed in tables. Apart from the engineering point of view, the present article has strong advantage over the published literature as the exact solutions obtained here can be used as a benchmark for comparison with numerical/approximate solutions and experimental data.